The Effect of TiO2 in Ceramic Product Glaze on the Photodegradation of Methylene Blue - eneng maryani (Universitas Padjadjaran, 2021)
Glaze is a coating on the surface of ceramic products such as tiles, sanitary ware and tableware. One of the functions of the glaze is to protect ceramic products from harmful chemicals such as dyes. For this purpose, the glaze material is added with other additives such as TiO2 which is a photocatalyst. n this study, silica sand and commercial glaze 107 with a ratio of 1: 1 were used as the main raw material for glaze with the addition of 0-5% titanium dioxide powder. The raw material for the glaze is wet ground in an alumina potmill for 24 hours. The results of these mills, dried in an oven at a temperature of 100 oC. The dried glaze contains silica as a-quartz and anatase TiO2. The percentage of decolorization (photodegradation) of the glaze to the methylene blue dye after 4 hours of UV exposure was carried out by measuring the absorption of non-degraded methylene blue using a UV-Vis spectrophotometer at a wavelength of 664 nm. Glaze without the addition of TiO2 showed a percent decolorization (photodegradation) of methylene blue of 71.55% which occurred mainly through the adsorption reaction of methylene blue by silica which is mostly contained in the glaze. The optimum value of percent decolorization is 88.49% obtained for glaze materials with the addition of 2% TiO2. The addition of TiO2 which exceeds the optimum value, causes a decrease in the percentage of decolorization (photodegradation) due to TiO22 aggregation on the surface of the silica adsorbent.